Adverse fetal and infant outcomes among HIV-infected women who received either nonnucleoside reverse transcriptase inhibitor-based or protease inhibitor-based antiretroviral therapy for prevention of mother-to-child transmission. (31st July 2018) - Masaba, Rose; Borkowf, Craig B.; Girde, Sonali; Zeh, Clement; Ndivo, Richard; Nyang'au, Isabella; Achola, Kevin; Thomas, Timothy K.; Lecher, Shirley Lee
Abstract : Background: For HIV-infected pregnant and breastfeeding women, antiretroviral therapy (ART) is known to reduce the mother's risk of passing the infection to her child. However, concerns remain about possible associations between various components of different ART regimens and adverse fetal and infant outcomes. As part of a clinical trial in western Kenya for the prevention of mother-to-child transmission (PMTCT) of HIV, pregnant women received one of two different ART regimens. Methods: The original PMTCT study conducted in Kenya enrolled 522 HIV-infected, ART-naive pregnant women. These women were assigned to receive an ART regimen that included either nevirapine, a nonnucleoside reverse transcriptase inhibitor (NNRTI), or nelfinavir, a protease inhibitor. This substudy involves 384 women from the original study who had baseline CD4 + cell counts at least 250 cells/μl, and compares the risks of adverse fetal and infant outcomes between the two ART regimens. Results: There were 386 live births (including multiples) and 7 (1.8%) stillbirths. Among live births, there were 67 preterm deliveries, 37 low-birth weight infants, and 14 infant deaths by 6 months. There were no statistically significant differences between the two ART regimens for any of the reported adverse outcomes. Conclusion: Although these data do not show significant differences between the NNRTI-based or protease inhibitor-based regimens in serious adverse fetal and infant outcomes, more studies need to be done and careful vigilance is needed to ensure infant safety.